The Vindication of the World: Essays Engaging with Stephen Phillips - Phillips, Stephen H.; Keating, Malcolm; Dasti, Matthew R. (Routledge Festschrifts in Philosophy, 2024)
IntroductionPart 1: Early and Classical Indian Philosophy1. Following Phillips'sLead: Fallacies, CriticalThinking, and ContemplationMatthew R. Dasti and Malcolm Keating2. SeventoOne: Fusing Vaiśeṣika'sCategorieswithAbhidharmaOntologyMark Siderits3. Is Indian Epistemology Externalist?John Taber4. Udayana on the Indefinability of DistinctnessNilanjan DasPart 2: Gaṅgeśa and Navya-Nyāya5. Gaṅgeśa and the Gettier ProblemJoel Feldman6. In Search of CertificationAnand Jayprakash Vaidya7. Is Nyāya Disjunctivist? The Ontology of IllusionJonardon Ganeri8. The Nyāya on TruthJ. L. ShawPart 3: Advaita Vedānta9. Metaphors forMāyā: Philosophical Illustrations in Śaṅkara's Advaita VedāntaNeil Dalal10. Phillips's Points and Padmapāda's Possible DefenseNirmalya Guha